Child maltreatment and sleep problems among adolescents in Ontario: A cross sectional study. (January 2020) - Turner, Sarah; Menzies, Caitlin; Fortier, Janique; Garces, Isabel; Struck, Shannon; Taillieu, Tamara; Georgiades, Katholiki; Afifi, Tracie O.
Abstract: Introduction: Child maltreatment has a negative impact on health and well-being. Healthy sleep patterns are an important indicator of health and are particularly important for adolescent growth and development. Few studies examine the relationship between child maltreatment and sleep problems using a general population, adolescent sample. The objective of the current study was to examine the relationship between five different types of child maltreatment and four sleep outcomes among adolescents. Methods: Data were from a subset of the Ontario Child Health Study 2014, a representative sample of 14 to 17- year-olds in Ontario, Canada (n=2, 910). Sexual abuse, physical abuse and exposure to intimate partner violence (EIPV) were measured using the Childhood Experiences of Violence Questionnaire (CEVQ). Emotional maltreatment and physical neglect were measured using items derived from survey questions designed for the National Longitudinal Study of Adolescent to Adult Health. Sleep outcomes included time it takes to fall asleep, waking during the night, and hours of sleep on weekdays and weekends. Models were adjusted for sociodemographic variables. Results: Findings indicate that all types of child maltreatment were associated with increased odds of taking more than 10 min to fall asleep (adjusted odds ratio [AOR]: 1.21–1.58), waking more often during the night (AOR: 1.62–5.73) and fewer hours slept on weekdays (adjusted beta [AB]: −0.39 to −0.15). Child sexual abuse, emotional maltreatment, and EIPV were associated with decreased hours of sleep on weekends (AB: −0.63 to −0.28). Conclusion: Preventing child maltreatment may improve sleep outcomes among adolescents, thereby improving overall health and well- being.